B1 SOX coordinate cell specification with patterning and morphogenesis in the early zebrafish embryo. - Yuichi Okuda; Eri Ogura; Hisato Kondoh; Yusuke Kamachi (PLoS Genetics)
The B1 SOX transcription factors SOX1/2/3/19 have been implicated in various processes of early embryogenesis. However, their regulatory functions in stages from the blastula to early neurula remain largely unknown, primarily because loss-of-function studies have not been informative to date. In our present study, we systematically knocked down the B1 sox genes in zebrafish. Only the quadruple knockdown of the four B1 sox genes sox2/3/19a/19b resulted in very severe developmental abnormalities, confirming that the B1 sox genes are functionally redundant. We characterized the sox2/3/19a/19b quadruple knockdown embryos in detail by examining the changes in gene expression through in situ hybridization, RT-PCR, and microarray analyses. Importantly, these phenotypic analyses revealed that the B1 SOX proteins regulate the following distinct processes: (1) early dorsoventral patterning by controlling bmp2b/7; (2) gastrulation movements via the regulation of pcdh18a/18b and wnt11, a non-canonical Wnt ligand gene; (3) neural differentiation by regulating the Hes-class bHLH gene her3 and the proneural-class bHLH genes neurog1 (positively) and ascl1a (negatively), and regional transcription factor genes, e.g., hesx1, zic1, and rx3; and (4) neural patterning by regulating signaling pathway genes, cyp26a1 in RA signaling, oep in Nodal signaling, shh, and mdkb. Chromatin immunoprecipitation analysis of the her3, hesx1, neurog1, pcdh18a, and cyp26a1 genes further suggests a direct regulation of these genes by B1 SOX. We also found an interesting overlap between the early phenotypes of the B1 sox quadruple knockdown embryos and the maternal-zygotic spg embryos that are devoid of pou5f1 activity. These findings indicate that the B1 SOX proteins control a wide range of developmental regulators in the early embryo through partnering in part with Pou5f1 and possibly with other factors, and suggest that the B1 sox functions are central to coordinating cell fate specification with patterning and morphogenetic processes occurring in the early embryo.